A Comparative Study of the Satisfaction of American and Mexican Operations - Slocum, John W. (Academy of Management Journal, 1971)
This study compared the perceptions of need satisfaction and importance for blue-collar workers in the USA and Mexico. Organizational and technological differences were controlled to isolate culture as the independent variable. Porter's need questionnaire was used to tap employees' attitudes. The data indicate that there were significant differences in nearly every need item score between the two countries. Mexican workers were more satisfied than their counterparts in the USA.